2017
DOI: 10.1016/j.conb.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-transmitter neurons in the mammalian central nervous system

Abstract: It is firmly established that many mammalian neurons release various combinations of amino acids, their derivatives, and other small molecules from presynaptic terminals in order to signal to their postsynaptic targets. Here we discuss recent findings about four types of multi-transmitter neurons – those that release GABA and acetylcholine (Ach); dopamine (DA) and GABA or glutamate; and glutamate and GABA. The mechanisms of co-release in each class differ and highlight the complex and dynamic nature of neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 68 publications
5
59
0
1
Order By: Relevance
“…Although we did not investigate the release of these transmitters in this work, the possible co-release of glutamate and GABA from single nerve terminals in the brain has been demonstrated extensively ( Beltrán and Gutiérrez, 2012;Galván and Gutiérrez, 2017;Noh et al, 2010;Root et al, 2014;Shabel et al, 2014;Yoo et al, 2016). Our findings support the existence of multitransmitter neurons in the zebrafish spinal cord, as was already established in the lamprey spinal cord (Fernández-López et al, 2012) and the mammalian brain (Granger et al, 2017;Tritsch et al, 2016). However, the co-expression and co-release of these diverse transmitter combinations in mammalian spinal neurons has yet to be confirmed.…”
Section: Discussionsupporting
confidence: 85%
“…Although we did not investigate the release of these transmitters in this work, the possible co-release of glutamate and GABA from single nerve terminals in the brain has been demonstrated extensively ( Beltrán and Gutiérrez, 2012;Galván and Gutiérrez, 2017;Noh et al, 2010;Root et al, 2014;Shabel et al, 2014;Yoo et al, 2016). Our findings support the existence of multitransmitter neurons in the zebrafish spinal cord, as was already established in the lamprey spinal cord (Fernández-López et al, 2012) and the mammalian brain (Granger et al, 2017;Tritsch et al, 2016). However, the co-expression and co-release of these diverse transmitter combinations in mammalian spinal neurons has yet to be confirmed.…”
Section: Discussionsupporting
confidence: 85%
“…Anatomical studies have suggested that the ChAT+ MFs located in lobules IX/X and the flocculus originate from medial vestibular nucleus (MVN) and nucleus prepositus hypoglossi (NPH) (Barmack et al, 1992b), whereas ChAT+ beaded fibers may originate from the pedunculopontine tegmental nuclei (PPTg) (Newman and Ginsberg, 1992; Ruggiero et al, 1997; Woolf and Butcher, 1989). Notably, for any of these sources it remains possible that other neurotransmitters are co-released with ACh as has been shown in other brain regions (Granger et al, 2017). However, based on our goal of measuring the longer timescale effects of ACh, we did not investigate the possibility of other fast transmitters that may also play a role during the initial phases of transient ACh release.…”
Section: Discussionmentioning
confidence: 98%
“…An alternative scenario is that different neuropeptides converge on a common excitatory intracellular signaling pathway in RoL1 neurons downstream of their specific metabotropic receptors, which could function in a degenerate manner (Marder, 2012;Nath et al, 2016). Given the prevalence of neuromodulator/amino-acid co-release throughout nervous systems (Schöne & Burdakov, 2012;Granger et al, 2017;Nusbaum et al, 2017), resolving these issues will be generally important for studies of neural circuit function across species and behaviors. Our brain-wide and hypothalamic cell typespecific imaging data both point towards a similar principle: neural activity patterns are widely distributed across cell types and brain areas, even during simple behaviors.…”
Section: Discussionmentioning
confidence: 99%